Parallel hierarchies for solving Single Source Shortest Path problem - Chomątek, Łukasz (Wydawnictwo Politechniki Łódzkiej, 2013)
The problem of route optimization is significant due to the fact of the high availablity of private transport as well as the need of efficient utilization of the corporate fleet. Optimal route can have different meaning for different users. In the existing algorithms designed for finding optimal route between two points on the map, hardly any preferences are reflected. In this article we present efficient algorithm for finding optimal route between points on the map which is designed to conforms Users’ needs.